M1V1 + M2V2 = M1V1' + M2V2'
where:
M1 is the mass of the large marble = 0.05 kg
V1 is the initial velocity of the large marble = 0.6 m/sec
M2 is the mass of the small marble = 0.03 kg
V2 is the initial velocity of the small marble = 0 m/sec (marble is at rest)
V1' is the final velocity of the large marble = -0.2 m/sec
V2' is the final velocity of the small marble that we want to calculate
Substitute with the givens in the above equation to get V2' as follows:
M1V1 + M2V2 = M1V1' + M2V2'
(0.05)(0.6) + (0.03)(0) = (0.05)(-0.2) + 0.03V2'
0.03 = -0.01 + 0.03V2'
0.03V2' = 0.03+0.01 = 0.04
V2' = 0.04/0.03
V2' = 1.334 m/sec